When to Start and Stop Bone-Protecting Medication for Preventing Glucocorticoid-Induced Osteoporosis - Hayes, Kaleen N.; Baschant, Ulrike; Hauser, Barbara; Burden, Andrea M.; Winter, Elizabeth M. (Frontiers in Endocrinology, 2021)
Glucocorticoid-induced osteoporosis (GIOP) leads to fractures in up to 40% of patients with chronic glucocorticoid (GC) therapy when left untreated. GCs rapidly increase fracture risk, and thus many patients with anticipated chronic GC exposures should start anti-osteoporosis pharmacotherapy to prevent fractures. In addition to low awareness of the need for anti-osteoporosis therapy among clinicians treating patients with GCs, a major barrier to prevention of fractures from GIOP is a lack of clear guideline recommendations on when to start and stop anti-osteoporosis treatment in patients with GC use. The aim of this narrative review is to summarize current evidence and provide considerations for the duration of anti-osteoporosis treatment in patients taking GCs based on pre-clinical, clinical, epidemiologic, and pharmacologic evidence. We review the pathophysiology of GIOP, outline current guideline recommendations on initiating and stopping anti-osteoporosis therapy for GIOP, and present considerations for the duration of anti-osteoporosis treatment based on existing evidence. In each section, we illustrate major points through a patient case example. Finally, we conclude with proposed areas for future research and emerging areas of interest related to GIOP clinical management.